2001
DOI: 10.1081/ncn-100002314
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Inhibitors – Oligonucleotide Phosphoramidates as Potential Therapeutic Agents

Abstract: We have designed, synthesized, and evaluated using physical, chemical and biochemical assays various oligonucleotide N3'-->P5' phosphoramidates, as potential telomerase inhibitors. Among the prepared compounds were 2'-deoxy, 2'-hydroxy, 2'-methoxy, 2'-ribo-fluoro, and 2'-arabino-fluoro oligonucleotide phosphoramidates, as well as novel N3'-->P5' thio-phosphoramidates. The compounds demonstrated sequence specific and dose dependent activity with IC50 values in the sub-nM to pM concentration range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 19 publications
(6 reference statements)
0
60
0
Order By: Relevance
“…Following this appealing scienti®c rationale, several classes of telomerase inhibitors were prepared and evaluated. Among the compounds tested were small molecules (Naasani et al, 1998(Naasani et al, , 1999Bare et al, 1998;Hisatake et al, 1999), compounds capable of interacting with DNA G-quadruplex structures (Neidle et al, 2000;Hurley et al, 2000), dominant negative hTERTderived proteins (Hahn et al, 1999), antisense RNA (Feng et al, 1995;Yamaguchi et al, 1999), and various types of oligonucleotides, including DNA phosphodiesters (Glukhov et al, 1998), 2-5A tethered phosphodiesters (Kondo et al, 1998), phosphorothioates (Norton et al, 1996;Matthes and Lehmann, 1999;Sharma et al, 1996), phosphoramidates (Gryaznov et al, 2001), 2'-O-Methyl and 2'-O-(Methoxy-ethyl) phosphorothioate chimera (Pitts and Corey, 1998;Elayadi et al, 2001), ribozymes (Wan et al, 1998), and PNA molecules (Norton et al, 1996). The e ects of DNA, PNA and 2'-modi®ed RNA oligonucleotides reportedly were sequence speci®c, unlike the activity of the majority of earlier generation of phosphorothioates oligomers (Matthes and Lehman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Following this appealing scienti®c rationale, several classes of telomerase inhibitors were prepared and evaluated. Among the compounds tested were small molecules (Naasani et al, 1998(Naasani et al, , 1999Bare et al, 1998;Hisatake et al, 1999), compounds capable of interacting with DNA G-quadruplex structures (Neidle et al, 2000;Hurley et al, 2000), dominant negative hTERTderived proteins (Hahn et al, 1999), antisense RNA (Feng et al, 1995;Yamaguchi et al, 1999), and various types of oligonucleotides, including DNA phosphodiesters (Glukhov et al, 1998), 2-5A tethered phosphodiesters (Kondo et al, 1998), phosphorothioates (Norton et al, 1996;Matthes and Lehmann, 1999;Sharma et al, 1996), phosphoramidates (Gryaznov et al, 2001), 2'-O-Methyl and 2'-O-(Methoxy-ethyl) phosphorothioate chimera (Pitts and Corey, 1998;Elayadi et al, 2001), ribozymes (Wan et al, 1998), and PNA molecules (Norton et al, 1996). The e ects of DNA, PNA and 2'-modi®ed RNA oligonucleotides reportedly were sequence speci®c, unlike the activity of the majority of earlier generation of phosphorothioates oligomers (Matthes and Lehman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…30 We found that GRN163 decreased TA in all cell lines and enhanced telomeric shortening in a lymphoma cell line (telomere length, 4.5 kb) after 33 days. Continuous GRN163 exposure of malignant cell lines with short telomeres (1.7-5.4 kb) resulted in the rapid dose-dependent induction of proliferative arrest and cell death, whereas up to 40 days of GRN163 treatment of cells with long telomere lengths did not influence proliferation.…”
Section: Introductionmentioning
confidence: 92%
“…GRN163 is resistant to hydrolysis by cellular nucleases and exhibits high thermodynamic stability. 30 Earlier biochemical assays demonstrated that GRN163 inhibits human telomerase in a sequence-specific manner, with IC 50 values in the sub-nanomolar range and IC 50 values of 0.5 M against solid tumor cell lines in the absence of uptake enhancers. 30 In the absence of exogenous uptake enhancers, 3Ј-fluoresceinlabeled GRN163 oligonucleotide was added to cultured cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference significantly contributes to making cancer cells more sensitive to telomerase inhibitors and may allow for a substantial therapeutic window for telomerase inhibition. One such inhibitor is GRN163L, a lipidated 13-mer oligonucleotide complementary to the RNA template region of human telomerase RNA (hTR) [175,176]. Its mechanism of action is not that of antisensemediated RNase H catalyzed hydrolysis but that it acts as a template antagonist, thus inhibiting telomerase activity.…”
Section: Targeting Senescencementioning
confidence: 99%